2020
DOI: 10.1016/j.ffa.2020.101659
|View full text |Cite
|
Sign up to set email alerts
|

Moments of Dirichlet L–functions with prime conductors over function fields

Abstract: We compute the second moment in the family of quadratic Dirichlet Lfunctions with prime conductors over F q [x] when the degree of the discriminant goes to infinity, obtaining one of the lower order terms. We also obtain an asymptotic formula with the leading order term for the mean value of the derivatives of L-functions associated to quadratic twists of a fixed elliptic curve over F q (t) by monic irreducible polynomials, which allows us to show that there exists a monic irreducible polynomial such that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…In a recent paper, Andrade, Jung and Shamesaldeen [2] conjectured the integral moments and ratios of quadratic Dirichlet L-functions over monic irreducible polynomials in F q [T ] and showed that their conjecture agrees with the asymptotic formulas obtained by Andrade and Keating [4] and Bui and Florea [8].…”
Section: If We Letmentioning
confidence: 87%
“…In a recent paper, Andrade, Jung and Shamesaldeen [2] conjectured the integral moments and ratios of quadratic Dirichlet L-functions over monic irreducible polynomials in F q [T ] and showed that their conjecture agrees with the asymptotic formulas obtained by Andrade and Keating [4] and Bui and Florea [8].…”
Section: If We Letmentioning
confidence: 87%
“…Recently, Bui and Florea [6] improved Andrade and Keating's result for the second moment and proved that…”
Section: The Function Field Settingmentioning
confidence: 89%
“…, χ P ∼ P log q P , while, along with Bui and Florea [5], in the same paper computed the second moment…”
Section: Introductionmentioning
confidence: 93%